Analysis of Marketing Public Relations Strategies in Increasing Competitiveness - Hadi Susanto, Septian; Wisudawaty, Hanna (PT ARRUS Intelektual Indonesia, 2024)
The marketing public relations (MPR) strategy is an integration of marketing and public relations strategies that can create a more holistic approach to building relationships with consumers and society. MPR is very important in a company, especially Badan Usaha Milik Negara (BUMN) company in maintaining its business continuity, because BUMN companies act as agents of value creators and agents of development, which means agents of development and drivers of economic growth in Indonesia (Thohir, 2023). The research in this study discusses the public relations markerting strategy of PT Pelabuhan Indonesia (Persero) Regional II Panjang in increasing competitiveness. The purpose of this research is to find out how the MPR strategy implemented by PT Pelabuhan Indonesia (Persero) Regional II Panjang and the role of MPR in increasing competitiveness. This research uses a qualitative approach with a phenomenological study method, collecting data from this research through interviews, observation, and documentation. This research is based on the theory of Three Way Strategies in public relations programs (Harris, 1998) and the theory of P.E.N.C.I.L.S Strategy in marketing public relations (Kotler and Keller, 2006: p.553). The results of this study state that the marketing public relations strategy of PT Pelabuhan Indonesia (Persero) Regional II Panjang in increasing competitiveness has been carried out systematically and is a routine agenda so that the strategy becomes efficient in increasing the competitiveness of the company. Therefore, until now PT Pelabuhan Indonesia (Persero) Regional II Panjang still dominates competition in the port industry and always provides positive performance.